The Politics of Migrant Resistance amid the Greek Economic Crisis. Issue 2 (20th August 2016) - Skleparis, Dimitris
Abstract: This paper focuses on a particular instance of migrant resistance: the hunger strike of three hundred irregular migrants in 2011 in Greece. It does not conceptualize the politics of migrant resistance as an isolated incidence of mobilization of irregular migrants against the government in support for their rights in existing institutions. By drawing on a set of fifty-two face-to-face semi-structured interviews with migrant protesters and organizers of the hunger strike, this paper rather argues that the politics of migrant resistance is performed in the daily lives and day-to-day activities of irregular migrants. It is performed by irregular migrants and those who stand in solidarity with them through the mundane production of information, tricks for survival, mutual care, social relations, services exchange, solidarity, and sociability, which challenge security policies and controls and establish an alternative form of life. The differential inclusion of irregular migrants in various social fields, and the leeway that this inclusion potentially creates in their daily lives and social relationships, enables irregular migrants to create ties with other agents/actors in dominated positions in their social fields, who possess and control the essential capital for the creation of these alternative modes of life.